Feasibility Study of Human Corneal Endothelial Cell Transplantation Using an In Vitro Human Corneal Model. Issue 6 (June 2018) - Rolev, Kostadin; O'Donovan, Dominic G.; Coussons, Peter; King, Linda; Rajan, Madhavan S.
Abstract : Purpose: To test the feasibility of a cell therapy approach to treat corneal endothelial (CE) disorders using an in vitro model of human corneal decompensation. Methods: A CE decompensation model was established by removal of the Descemet membrane/endothelium complex from cadaveric human corneas in an air interface organ culture system (group 2) and compared with normal corneas (group 1). The posterior stroma of decompensated corneas was seeded with immortalized human corneal endothelial cells (HCEC-12) in group 3 and passage 0 primary human CE cells in group 4 corneas. Functional effects on stromal thickness were determined with histological analysis 3 to 10 days after cell therapy treatment. Results: Removal of the Descemet membrane/endothelium complex in group 2 corneas resulted in a stromal thickness of 903 ± 86 μm at 12 hours compared with 557 ± 72 μm in group 1 corneas. Stromal thickness reduced from 1218 ± 153 μm to 458 ± 90 μm (63% ± 6%, P = 0.001) after cell transplantation in group 3 and from 1100 ± 86 μm to 489 ± 94 μm (55% ± 7%, P = 0.00004) in group 4. Posttransplantation histology demonstrated formation of a monolayer of corneal endothelium attached to the posterior stromal surface. Conclusions: Direct transplantation of cultured human CE cells and immortalized HCEC-12 to bare posterior corneal stroma resulted in formation of an endothelial monolayer and restoration of stromal hydration to physiological thickness, demonstrating the feasibility of cell therapy in treatment of CE decompensation in a human in vitro model.